RELIABILITY ANALYSIS OF DATA FUSION BASED ON A MIXED BASIS DISTRIBUTION METHOD - ZHANG XiaoJie; TANG JiaYin (Jixie qiangdu)
Aiming at the life data information of multiple types of testing sources for the same product, a mixed base distribution constructed to achieve three-source data fusion, and at the same time, the overall distribution density function of the life data source was estimated. And the iterative formula of the maximum likelihood estimation of each unknown parameter in the parameter vectors of the mixed basis distribution density function was obtained based on the EM algorithm. At the same time, the estimated value of each parameter was given by using the sample weighted by Bootstrap method, the density function analysis of the mixed basis distribution was determined, and the product reliability analysis was completed. The calculation example verified the feasibility and effectiveness of this type of model.